AGRICULTURAL RECYCLING OF FISH FARMING SLUDGE FROM EXCAVATED PONDS IN RAMAL DO BANCO, RIO PRETO DA EVA, AMAZONAS - da Silva, Luiz Carlos; da Costa, Francimara Souza; Pereira, Bruno Fernando Faria (Editora Impacto Científico, 2025)
The generation and recycling of waste are major challenges for humanity. This is the case of fish farming sludge from excavated ponds, composed of a mixture of sediment from applied inputs and fish feces combined with the pond bottom soil. The accumulation of sludge in ponds due to poor maintenance of water oxygenation can create environmental liabilities on properties. This issue was identified in Ramal do Banco in 2019, and based on the observations, the possibility of using the accumulated sludge as a soil conditioner for cultivated land was considered. This practice would replace the unregulated disposal methods currently used in the area. In this context, this study aimed to: i) characterize the type of agriculture practiced and the current use of fish farming sludge in that community; ii) describe the methods and results of extension activities carried out there, and establish recommendations for recycling fish farming sludge from excavated ponds in the cultivation of tall or staked plant species in Ramal do Banco, Rio Preto da Eva, Amazonas. The agriculture practiced in Ramal do Banco is both commercial and subsistence-based and includes a wide variety of species suitable for recycling fish farming sludge produced in the community. According to the analyzed attributes, the fish farming sludge has the physical, chemical, and biological quality required for recycling in agricultural soils. Therefore, doses and methods for recycling fish farming sludge in the cultivated species of Ramal do Banco were calculated and will be included in an agricultural recycling manual to be published in 2025. DOI: https://doi.org/10.56238/edimpacto2025.080-004